Firefighters Are More Physically Active On-Duty Compared to Off-Duty - Barry, Allison M. (Int J Environ Res Public Health, 2020)
Physical inactivity, coupled with increasing obesity levels, in firefighters plays a key role in aggregated cardiovascular events. The purpose of this study was to investigate device-measured physical activity (PA) for firefighters while on- and off-duty to have a clearer understanding of their overall PA level. Methods: Twenty-nine career firefighters participated in this non-experimental, within-subjects study by wearing an accelerometer to assess PA intensities and step-count. Obesity was classified using body mass index (BMI). Dependent t-tests were used to examine mean differences in PA intensities when on- and off-duty. Pearson product-moment correlations were used to assess the association between PA intensities when on and off-duty. Results: According to the World Health Organization BMI categorizations, 20 firefighters were overweight, 9 were obese, and, thus, none were normal weight. Only light PA (LPA) was statistically significant (p = 0.026) for on- and off-duty days with a small-to-medium effect size (d = 0.47), meaning that on average, firefighters performed more minutes of LPA when on-duty compared to off. There was a significant difference between on- (9060.2 ± 2636.4) and off-duty (7495.3 ± 2835.8) daily step counts (p = 0.011). Conclusion: As the results demonstrate, there is a dire need for increased PA levels in firefighters while on- and off-duty.